Positive electrode active material and preparation method and application thereof
By introducing a cladding layer into the positive electrode active material and optimizing the particle size of the positive electrode matrix material, the problem of insufficient dispersion of the positive electrode active material particles in the dry process is solved, and a higher positive electrode sheet compaction density and battery energy density are achieved.
Patent Information
- Application Number
- CN202411998433.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The dry process faces the problem of insufficient particle dispersion in the application of positive electrode active materials, resulting in uneven distribution of active materials, affecting the compaction density of the positive electrode sheet and the energy density of the battery.
A positive electrode active material including a positive electrode matrix material and a cladding layer is used. The chemical formula of the cladding layer is LixMyPO4, wherein M includes at least one of Ti, V, Co, and Zn, 0
The particle dispersion and fluidity of the positive electrode active material are improved, the compaction density of the positive electrode sheet is enhanced, thereby improving the energy density of the battery, while maintaining the mechanical strength and conductive properties of the material.
Smart Images

Figure CN119812268A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a positive electrode active material and a preparation method and application thereof. Background Art
[0002] In the continuous development of lithium-ion battery technology, the selection and optimization of positive electrode active materials play a vital role in improving battery performance. In practical applications, the selection of production processes is crucial to the performance of material properties. Although the traditional wet process performs well in particle dispersion and uniformity, it has a greater impact on the environment and high production costs. In contrast, the dry process has become a potential alternative due to its advantages of reducing solvent use, reducing energy consumption and low production costs.
[0003] However, the dry process faces the problem of insufficient particle dispersion in the application of positive electrode active materials. Due to the lack of liquid medium assistance, the positive electrode active materials are prone to agglomeration during the mixing process, resulting in uneven distribution of active materials, which in turn affects the compaction density of the positive electrode sheet and the overall energy density of the battery. In addition, the friction between particles is large, which affects the fluidity of the material, further reducing the compaction density of the dry electrode, thereby restricting the improvement of the battery energy density. Therefore, finding effective methods to improve the particle dispersion of positive electrode active materials in the dry electrode process, increase the compaction density of the positive electrode sheet, and thus increase the energy density of the battery has become a key issue that needs to be urgently addressed in the current field of battery material research. Summary of the invention
[0004] The main purpose of the present invention is to provide a positive electrode active material agent, the particles of which have good dispersibility and can increase the compaction density of the positive electrode sheet, thereby increasing the energy density of the battery.
[0005] The present invention also provides a method for preparing a positive electrode active material, which can prepare the positive electrode active material and has simple process and low cost.
[0006] The present invention also provides a positive electrode sheet, comprising the positive electrode active material. Therefore, the positive electrode sheet has a higher compaction density and is applied to a battery to enable the battery to have a higher energy density.
[0007] The present invention also provides a method for preparing a positive electrode sheet, which can prepare the positive electrode sheet and has simple process and low cost.
[0008] The present invention also provides a battery, comprising the positive electrode sheet, so the battery has a higher energy density.
[0009] In a first aspect, the present invention provides a positive electrode active material, comprising a positive electrode base material and a coating layer present on the surface of the positive electrode base material;
[0010] The compression degree S of the positive electrode active material is 0.45≤S≤0.55.
[0011] As the positive electrode active material described above, the chemical formula of the coating layer is Li x M y PO4, wherein M includes at least one of Ti, V, Co, and Zn, 0<x≤0.2, 0.5<y<1.5.
[0012] For the positive electrode active material as described above, the coating layer has a thickness of 1 nm to 5 nm.
[0013] For the positive electrode active material as described above, the median particle size D50 of the positive electrode matrix material is 500nm-1500nm.
[0014] In the positive electrode active material as described above, the positive electrode matrix material includes a lithium-containing phosphate.
[0015] In the positive electrode active material as described above, the lithium-containing phosphate includes at least one of lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, and lithium iron vanadium manganese phosphate.
[0016] The positive electrode active material as described above, wherein the mass percentage of the positive electrode matrix material in the positive electrode active material is 99.4%-99.98%;
[0017] And / or, the mass percentage of the coating layer in the positive electrode active material is 0.02%-0.6%.
[0018] The positive electrode active material as described above, wherein the loose packing density of the positive electrode active material is 0.35-0.45 g / cm 3 ;
[0019] And / or, the tap density of the positive electrode active material is 0.75-0.85 g / cm 3 .
[0020] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described above, comprising the following steps:
[0021] 1) Activating the positive electrode matrix material to obtain a first intermediate;
[0022] 2) stirring the solution including the first intermediate, the M source and the P source uniformly, and filtering to obtain a second intermediate; wherein the M source is a metal organic compound including the M element;
[0023] 3) Sintering the second intermediate to obtain the positive electrode active material; wherein the sintering temperature is 450° C.-650° C.
[0024] The method for preparing the positive electrode active material as described above, wherein the total molar ratio of the positive electrode matrix material to the M source and the P source is (200-3000):1;
[0025] And / or, the sintering treatment time is 6h-18h;
[0026] And / or, the D50 of the capping agent is less than or equal to 20 nm.
[0027] In a third aspect, the present invention provides a positive electrode sheet, comprising the positive electrode active material as described above or the positive electrode active material prepared by the method for preparing the positive electrode active material as described above.
[0028] The positive electrode sheet as described above has a compaction density greater than or equal to 2.3 g / m 3 .
[0029] In a fourth aspect, the present invention provides a method for preparing the positive electrode sheet as described above, comprising the following steps:
[0030] 1) Forming a raw material containing a positive electrode active material into a self-supporting film;
[0031] 2) Compounding the self-supporting film and the positive electrode current collector to obtain the positive electrode sheet.
[0032] In a fifth aspect, the present invention provides a battery, comprising the positive electrode sheet as described above or a positive electrode sheet prepared by the method for preparing the positive electrode sheet as described above.
[0033] The compression degree S of the positive electrode active material provided by the present invention satisfies 0.45≤S≤0.55, has moderate compressibility during the compaction process, can reduce the friction of the positive electrode active material, help reduce excessive contact and agglomeration between particles, make the particles more dispersed, and improve the fluidity of the positive electrode active material, so that the particles can be more evenly filled into the positive electrode sheet during the compaction process, which helps to increase the compaction density of the positive electrode sheet, thereby improving the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1is a scanning electron microscope image of a cross section of the positive electrode active material of Example 2 of the present invention;
[0036] Figure 2 This is a scanning electron microscope image of the cross section of the positive electrode active material of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In the continuous evolution of lithium-ion battery technology, cathode active materials play a vital role in batteries. For example, lithium iron manganese phosphate (LFMP) cathode active materials have attracted widespread attention due to their high energy density and cost-effectiveness. In theory, LFMP has an energy density 15%-20% higher than lithium iron phosphate (LFP), while the cost is only 5%-6% higher. This makes it an important upgrade direction for phosphate-based lithium-ion batteries, especially in the modern battery industry that pursues higher energy density and cost efficiency.
[0039] In the dry electrode preparation process, the uniform dispersion of LFMP particles becomes a major difficulty. Compared with the wet process, although the dry process has the advantages of reducing solvent use, energy consumption and production costs, its shortcomings in particle dispersion limit its wide application in LFMP materials. In the dry process, due to the lack of the assistance of liquid medium, LFMP particles are prone to agglomeration during the mixing process, resulting in uneven distribution of active substances and affecting the compaction density of the positive electrode. In addition, the friction between particles is large, which affects the fluidity of the material and further reduces the compaction density of the dry electrode, thereby restricting the improvement of the battery energy density. These technical bottlenecks limit the performance of LFMP materials in lithium-ion batteries, especially for high-performance battery applications that seek high energy density and long cycle life.
[0040] Based on this, in the first aspect, the present invention provides a positive electrode active material, including a positive electrode base material and a coating layer present on the surface of the positive electrode base material; the compression degree S of the positive electrode active material is 0.45≤S≤0.55, for example, it can be 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55 or a range consisting of any two of them.
[0041] The positive electrode active material provided by the present invention has a coating layer on the surface of the positive electrode matrix material, and the compression degree S of the positive electrode active material is 0.45≤S≤0.55, which can improve the dispersibility of the positive electrode active material, thereby improving the compaction density of the positive electrode sheet, and further improving the energy density of the battery. This is because: the compression degree of the positive electrode active material is within the above range, which means that the positive electrode active material has moderate compressibility during the compaction process, which can reduce the friction of the positive electrode active material, help reduce excessive contact and agglomeration between particles, make the particles more dispersible, and improve the fluidity of the positive electrode active material, so that the particles can be more evenly filled into the positive electrode sheet during the compaction process, which helps to improve the compaction density of the positive electrode sheet. At the same time, particles with good dispersibility can form a tighter stacking structure, reduce the gaps between particles, thereby improving the compaction density of the positive electrode sheet, and further improving the energy density of the battery. And the appropriate compression degree can also maintain the mechanical strength and conductivity of the material to a certain extent, ensuring that the positive electrode sheet has good stability and conductivity during the cycle.
[0042] In addition, the coating layer on the surface of the positive electrode matrix material can reduce the direct contact and agglomeration tendency between particles, which is conducive to maintaining the uniform distribution of particles and improving the dispersion of materials. It can also increase the particle strength of the positive electrode active material and avoid the problem of easy breakage of the positive electrode active material in the subsequent dry process of preparing the positive electrode sheet.
[0043] It can be understood that the compression degree S can be used to characterize the magnitude of the friction force of the positive electrode active material, which can be calculated by the formula S=(tapped density-loose packing density) / tapped density. Specifically, the compression degree S of the positive electrode active material can be calculated by testing the tap density and loose packing density of the positive electrode active material and then substituting them into the above formula.
[0044] The present invention does not limit the type of positive electrode matrix material, and the positive electrode active material commonly used in the art can be used.
[0045] The present invention does not limit the type of coating layer, and the coating layer commonly used in the art can be used.
[0046] The compression degree S of the positive electrode active material provided by the present invention satisfies 0.45≤S≤0.55, has moderate compressibility during the compaction process, can reduce the friction of the positive electrode active material, help reduce excessive contact and agglomeration between particles, make the particles more dispersed, and improve the fluidity of the positive electrode active material, so that the particles can be more evenly filled into the positive electrode sheet during the compaction process, which helps to increase the compaction density of the positive electrode sheet, thereby improving the energy density of the battery.
[0047] In some embodiments of the present invention, the chemical formula of the coating layer is Li x M yPO4, wherein M includes at least one of Ti, V, Co, and Zn, 0<x≤0.2, for example, it can be 0.01, 0.03, 0.05, 0.08, 0.1, 0.13, 0.15, 0.17, 0.2 or a range consisting of any two thereof. 0.5<y<1.5, for example, it can be 0.51, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.49 or a range consisting of any two thereof. The chemical formula of the coating layer can be Li 0.2 Ti 0.7 PO4、Li 0.02 Zn 1.49 PO4、Li 0.08 Co 1.46 PO4、Li 0.15 V 0.57 PO4、Li 0.1 V 0.3 Co 0.7 PO4 or any two of them.
[0048] The chemical formula of the coating layer of the present invention is Li x M y PO4, during the high-temperature sintering process, the diffusion rate of M ions and Li ions on the surface of the positive electrode active material is high, which helps to form a uniform and continuous coating layer, reduce the surface roughness, and the coating layer has a lower surface energy, which helps it to spread and adhere evenly on the surface of the positive electrode active material. Materials with low surface energy are more likely to form a smooth surface, improve the dispersion of particles, and help to increase the compaction density of the positive electrode sheet, thereby improving the energy density of the battery.
[0049] In some embodiments of the present invention, the thickness of the coating layer is 1 nm-5 nm, for example, it can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm or a range consisting of any two thereof.
[0050] It can be understood that the thickness of the coating layer will greatly affect the electronic conductivity of the positive electrode active material, thereby affecting the cycle performance of the battery. The coating layer in the present invention has a suitable coating thickness, which can take into account the conduction of both electrons and ions.
[0051] In one embodiment, the thickness of the composite coating layer is controlled to be 1nm-5nm, which is within a suitable range. The appropriate coating layer thickness can inhibit the growth of particles and reduce the diffusion distance of lithium ions. In addition, the appropriate coating layer thickness has excellent conductivity, which is conducive to the transmission of electrons and improves the electronic conductivity of the positive electrode active material, thereby improving the cycle performance of the battery. In addition, the appropriate coating layer thickness can further reduce the direct contact and agglomeration tendency between particles, which is conducive to maintaining the uniform distribution of particles and improving the dispersibility of materials. It can also increase the particle strength of the positive electrode active material, avoid the problem of easy breakage of the positive electrode active material in the subsequent dry process for preparing the positive electrode sheet, thereby increasing the compaction density of the positive electrode sheet and increasing the energy density of the battery.
[0052] The present invention does not limit the testing method of the coating layer thickness. For example, the coating layer of the positive electrode active material can be measured by scanning electron microscope.
[0053] The thickness of the coating layer in the present invention is 1nm-5nm. Within a suitable range, the thickness of the coating layer can effectively increase electron transfer without affecting ion transmission, and can improve the dispersibility of the material. When used in lithium-ion batteries, it can improve the cycle performance and energy density of lithium-ion batteries.
[0054] In some embodiments of the present invention, the median particle size D50 of the positive electrode matrix material is 500 nm-1500 nm, for example, it can be 500 nm, 800 nm, 1000 nm, 1200 nm, 1500 nm or a range consisting of any two thereof.
[0055] The median particle size D50 of the positive electrode matrix material in the present invention is within the above range, which is conducive to the uniform distribution and close packing of particles in the positive electrode sheet, improves the compaction density and structural stability of the positive electrode sheet, and can also reduce the side reaction between the positive electrode active material and the electrolyte, reduce the risk of thermal runaway, and improve the safety of the battery.
[0056] In some embodiments of the present invention, the positive electrode matrix material includes a lithium-containing phosphate.
[0057] Furthermore, the lithium-containing phosphate includes at least one of lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, and lithium iron vanadium manganese phosphate.
[0058] The type of the positive electrode matrix material in the present invention is within the above range, has good thermal stability and chemical stability, can reduce the risk of thermal runaway and fire of the battery, and improve the safety of the battery. It also remains stable during the charge and discharge process, reduces the volume change and structural damage of the material, thereby extending the cycle life of the battery. The lithium phosphate can adjust the voltage platform, energy density and other properties of the battery.
[0059] In some embodiments of the present invention, the mass percentage of the positive electrode matrix material in the positive electrode active material is 99.4%-99.98%, for example, it can be 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, 99.92%, 99.95%, 99.98% or any two thereof.
[0060] In some embodiments, the mass percentage of the coating layer in the positive electrode active material is 0.02%-0.6%, for example, it can be 0.02%, 0.05%, 0.06%, 0.08%, 0.1%, 0.2%, 0.3%, 0.5%, 0.6% or any two thereof.
[0061] It can be understood that the positive electrode matrix material is the main active component of the battery. A higher mass percentage of the positive electrode matrix material can ensure that the battery has a higher energy density and can store more energy. A lower mass percentage of the coating layer can still effectively cover the surface of the positive electrode matrix material, improve thermal stability and chemical stability, prevent the risk of side reactions and thermal runaway, and improve the dispersion of the material, thereby increasing the compaction density of the positive electrode sheet and thus the energy density of the battery.
[0062] In some embodiments of the present invention, the loose packing density of the positive electrode active material is 0.35-0.45 g / cm 3 , for example, can be 0.35 g / cm 3 , 0.36g / cm 3 , 0.38g / cm 3 , 0.40g / cm 3 , 0.42g / cm 3 , 0.45g / cm 3 Or a range consisting of any two of them.
[0063] In some embodiments, the tap density of the positive electrode active material is 0.75-0.85 g / cm 3 , for example, can be 0.75 g / cm 3 , 0.77g / cm 3 , 0.79g / cm 3 、0.81g / cm 3 , 0.83g / cm 3 , 0.85g / cm 3 Or a range consisting of any two of them.
[0064] The loose packing density and tap density of the positive electrode active material in the present invention are within the above ranges, which is conducive to obtaining a positive electrode active material with a compression degree S of 0.45≤S≤0.55, which can improve the particle dispersibility of the positive electrode active material, increase the compaction density of the positive electrode sheet, and enhance the energy density of the battery.
[0065] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described above, comprising the following steps:
[0066] 1) Activating the positive electrode matrix material to obtain a first intermediate;
[0067] 2) stirring the solution including the first intermediate, the M source and the P source uniformly, and filtering to obtain a second intermediate; wherein the M source is a metal organic compound including the M element;
[0068] 3) Sintering the second intermediate to obtain the positive electrode active material; wherein the sintering temperature is 450° C.-650° C.
[0069] In step 1), the present invention can use conventional methods in the art to prepare the positive electrode matrix material, and activate the positive electrode matrix material. For example, the positive electrode matrix material can be ultrasonically cleaned or plasma treated to clean the surface of the positive electrode matrix material and increase the active sites to obtain the first intermediate.
[0070] In step 2), the first intermediate, the M source, and the P source are dissolved in a solution, for example, a mixed solution of ethanol and water, and stirred evenly so that the M element and the P element are attached to the surface of the first intermediate. The M source is a metal organic compound including the M element, for example, tetrabutyl titanate, diethyl zinc, cyclopentadienyl cobalt, and the P source is for example diammonium dihydrogen phosphate. The mixture is filtered to obtain a second intermediate.
[0071] In step 3), the second intermediate obtained above is sintered, and after sintering, it is naturally cooled to room temperature to obtain the positive electrode active material. During the sintering process, the M element and the P element will attract a part of the Li ions in the bulk phase to embed into the structure, forming Li x M y PO4 olivine structure. The sintering temperature is 450°C-600°C, for example, 450°C, 500°C, 520°C, 550°C, 570°C, 600°C or any two thereof.
[0072] The preparation method provided by the present invention can prepare the positive electrode active material of the first aspect, and the positive electrode active material has good dispersibility, which can increase the compaction density of the positive electrode sheet and improve the energy density of the battery.
[0073] In some embodiments of the present invention, the total molar ratio of the positive electrode matrix material to the M source and the P source is (200-3000):1, for example, it can be 200:1, 500:1, 600:1, 800:1, 1000:1, 2000:1, 3000:1 or a range consisting of any two of them.
[0074] In some embodiments, the sintering treatment time is 6 hours to 18 hours, for example, it can be 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 15 hours, 18 hours or a range consisting of any two thereof.
[0075] In the present invention, the total molar ratio of the positive electrode matrix material to the M source and the P source is within the above range, and a positive electrode matrix material and a coating layer with an appropriate mass ratio can be obtained, which can improve the dispersibility of the positive electrode active material, increase the compaction density of the positive electrode sheet, and thus improve the energy density of the battery.
[0076] The sintering time in the present invention is within the above range, which is conducive to eliminating defects and stress in the material, promoting the improvement of the crystal structure, and improving the electrochemical performance of the material. It can also improve the thermal stability and chemical stability of the material, help form a good conductive network, and improve the electronic and ionic conductivity of the material, thereby improving the rate performance of the battery.
[0077] In a third aspect, the present invention provides a positive electrode sheet, comprising the positive electrode active material as described above or the positive electrode active material prepared by the method for preparing the positive electrode active material as described above.
[0078] Since the positive electrode sheet provided by the present invention includes the above-mentioned positive electrode active material, the positive electrode sheet has a higher compaction density and is used in a battery to improve the energy density of the battery.
[0079] In some embodiments of the present invention, the compaction density of the positive electrode sheet is greater than or equal to 2.3 g / m 3 , for example, it can be 2.3g / m 3 , 2.32g / m 3 , 2.34g / m 3 , 2.36g / m 3 , 2.38g / m 3 , 2.39g / m 3 , 2.4g / m 3 , 2.45g / m 3 , 2.5g / m 3 , 2.55g / m 3 , 2.6g / m 3 Or a range consisting of any two of them.
[0080] The compaction density of the positive electrode sheet in the present invention is within the above range, which can further improve the energy density of the battery.
[0081] In a fourth aspect, the present invention provides a method for preparing the positive electrode sheet as described above, comprising the following steps:
[0082] 1) Forming a raw material containing a positive electrode active material into a self-supporting film;
[0083] 2) The self-supporting film and the positive electrode current collector are compounded to obtain a positive electrode sheet.
[0084] In step 1 of the present invention, the positive electrode active material, the conductive agent and the binder, such as polytetrafluoroethylene (PTFE), are prepared in a mass percentage ratio of 95:2.5:2.5 for standby use, and the positive electrode active material and the conductive agent are added to a dry mixer and mixed for 20 min-60 min, and then the binder is added and mixed for 20 min-60 min to obtain a mixed raw material. The mixed raw material is put into a mixer and mixed for 0.5 h-1.5 h, and the material is fiberized to obtain a mixed product. The mixed product is subjected to four hot rolling presses, wherein the hot rolling temperature is 160°C-220°C, to obtain a self-supporting film with uniform thickness, also known as a self-supporting electrode film.
[0085] In step 2), the self-supporting film is placed on at least one surface of a positive electrode current collector, such as a carbon-coated aluminum foil, which can be any surface of the positive electrode current collector or the upper and lower surfaces of the positive electrode current collector. The self-supporting film is heated and cured by a hot roller press to firmly adhere to the positive electrode current collector, i.e., composite, to obtain a positive electrode sheet.
[0086] The preparation method of the present invention can prepare the positive electrode sheet of the third aspect, and the positive electrode sheet has a high compaction density and is used in batteries to improve the energy density of the batteries.
[0087] In a fifth aspect, the present invention provides a battery, comprising the positive electrode sheet as described above or a positive electrode sheet prepared by the method for preparing the positive electrode sheet as described above. The battery has the advantages corresponding to the above positive electrode sheet, which will not be described in detail.
[0088] The battery of the present invention includes a separator, a negative electrode and an electrolyte in addition to a positive electrode sheet. The composition of the negative electrode sheet can refer to conventional negative electrode sheets in the art, and the separator can also be a separator conventionally used in the art, such as a PP film, a PE film, etc.
[0089] The battery of the present invention can be prepared by conventional methods in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and then a battery cell can be obtained through a stacking or winding process, and then the above-mentioned battery can be obtained through baking, liquid injection, formation, packaging and other processes.
[0090] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0091] Example 1
[0092] The method for preparing the positive electrode active material of this embodiment comprises the following steps:
[0093] 1) Mix manganese carbonate, lithium hydroxide and iron phosphate, control the molar ratio of Mn:Fe to 0.6:0.4, and then add deionized water to adjust the solid content of the slurry to 35%.
[0094] 2) After the slurry is evenly mixed, add it to the coarse grinder, set the speed to 1500r / min, and the time is 1h. After the coarse grinding, transfer it to the sand mill for sand grinding, set the speed to 1500r / min, and the time is 2h. After the sand grinding, the slurry is slowly transported to the spray drying tower for drying. The inlet temperature is set to 200℃, the outlet temperature is set to 100℃, the compressed air pressure is 0.4MPa, and the drying time is 7h. The powder particles obtained after spray drying are placed in a tubular furnace and sintered under the protection of nitrogen. The temperature is controlled at 280℃ and the sintering time is 4h to obtain the positive electrode matrix material LiFe 0.4 Mn 0.6 PO4, among which LiFe 0.4 Mn 0.6 The median particle size D50 of PO4 is 1387 nm.
[0095] 3) For the positive electrode matrix material LiFe 0.4 Mn 0.6 PO4 was ultrasonically cleaned and plasma surface activated to obtain a first intermediate. M source tetrabutyl titanate and P source diammonium phosphate were dissolved in a mixed solution of ethanol and water to obtain a solution. The first intermediate was added to the solution and stirred evenly and then filtered to obtain a second intermediate. The second intermediate was sintered at a controlled sintering temperature of 600°C and a sintering time of 12 hours. The positive electrode matrix material LiFe 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 200:1. After sintering, it is naturally cooled to room temperature to obtain a positive electrode active material. The positive electrode active material includes a positive electrode base material and a coating layer on the surface of the positive electrode base material. The chemical formula of the coating layer is Li 0.2 Ti 0.7 PO4, the thickness of the coating layer is 5nm, the mass percentage of the positive electrode matrix material in the positive electrode active material is 99.577%, the mass percentage of the coating layer in the positive electrode active material is 0.423%, and the loose bulk density of the positive electrode active material is 0.41g / cm 3 , tap density is 0.79g / cm 3 , the compression degree S is 0.48.
[0096] Example 2
[0097] The preparation method of the positive electrode active material in Example 2 is basically the same as that in Example 1, except that the positive electrode matrix material LiFe is changed in step 3). 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 3000:1, and the chemical formula of the coating layer is Li 0.02 Ti 0.745 PO4.
[0098] Example 3
[0099] The preparation method of the positive electrode active material in Example 3 is basically the same as that in Example 1, except that the positive electrode matrix material LiFe is changed in step 3). 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 300:1, and the chemical formula of the coating layer is Li 0.18 Ti 0.705 PO4.
[0100] Example 4
[0101] The preparation method of the positive electrode active material in Example 4 is basically the same as that in Example 1, except that the sintering temperature in step 3) is changed to 580°C and the time is 12h. The positive electrode matrix material is LiFe 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 2500:1, and the chemical formula of the coating layer is Li 0.04 Ti 0.74 PO4.
[0102] Example 5
[0103] The preparation method of the positive electrode active material in Example 5 is basically the same as that in Example 1, except that the sintering temperature in step 3) is changed to 550°C and the time is 13h. The positive electrode matrix material is LiFe 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 200:1, and the chemical formula of the coating layer is Li 0.2 Ti 0.7 PO4.
[0104] Example 6
[0105] The preparation method of the positive electrode active material in Example 6 is basically the same as that in Example 1, except that the sintering temperature in step 3) is changed to 600°C and the time is 18h. The positive electrode matrix material LiFe 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 800:1, and the chemical formula of the coating layer is Li 0.1 Ti 0.725 PO4.
[0106] Example 7
[0107] The preparation method of the positive electrode active material in Example 7 is basically the same as that in Example 1, except that the sintering temperature in step 3) is changed to 550°C and the time is 14h. The positive electrode matrix material is LiFe 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 1000:1, and the chemical formula of the coating layer is Li 0.14 Ti 0.715 PO4.
[0108] Example 8
[0109] The preparation method of the positive electrode active material of Example 8 is basically the same as that of Example 1, except that the sintering temperature in step 2) is changed to 450° C. and the time is changed to 6 h, and the median particle size D50 of the obtained positive electrode matrix material is 956 nm.
[0110] Example 9
[0111] The preparation method of the positive electrode active material of Example 9 is basically the same as that of Example 1, except that the sintering temperature in step 2) is changed to 500° C. and the sintering time is changed to 18 h, and the median particle size D50 of the obtained positive electrode matrix material is 1316 nm.
[0112] Example 10
[0113] The preparation method of the positive electrode active material in Example 10 is basically the same as that in Example 1, except that the positive electrode matrix material is changed to lithium iron phosphate, the median particle size D50 is 681 nm, and the chemical formula of the coating layer is Li 0.05 Ti 0.7375 PO4.
[0114] Embodiment 11
[0115] The preparation method of the positive electrode active material in Example 11 is basically the same as that in Example 1, except that the positive electrode matrix material is changed to lithium vanadium phosphate, the median particle size D50 is 598nm, and the chemical formula of the coating layer is Li 0.06 Ti 0.735 PO4.
[0116] Example 12
[0117] The preparation method of the positive electrode active material in Example 12 is basically the same as that in Example 1, except that the M source in step 3) is changed to diethyl zinc, and the chemical formula of the coating layer is Li 0.2 Zn 1.4 PO4.
[0118] Example 13
[0119] The preparation method of the positive electrode active material in Example 13 is basically the same as that in Example 1, except that the M source in step 3) is changed to cyclopentadienyl cobalt, and the chemical formula of the coating layer is Li 0.4 Co 1.3 PO4.
[0120] Comparative Example 1
[0121] The positive electrode active material of Comparative Example 1 is LiFe 0.4 Mn 0.6 PO4, without surface coating.
[0122] Comparative Example 2
[0123] The preparation methods of the positive electrode active materials of Comparative Example 2 and Example 1 are basically the same, except that the M source in step 3) is changed to Ti powder. Ti powder cannot melt and coat the surface of the positive electrode matrix material, but can play a certain effect as lubricating particles.
[0124] Comparative Example 3
[0125] The preparation method of the positive electrode active material of Comparative Example 3 is basically the same as that of Example 1, except that the sintering temperature in step 3) is changed to 200°C and the time is 4h. The positive electrode matrix material LiFe 0.4 Mn 0.6 The total molar ratio of PO4 to M source and P source is 5000:1, and the chemical formula of the coating layer is Li 0.001 Ti 0.74975 PO4.
[0126] Test example:
[0127] 1. Loose bulk density BD: When adding samples, use a spoon to place the positive electrode active material powder of the embodiment and the comparative example on the funnel screen, and use a brush to slowly stir the sample to make it fall evenly into the screen until the sample in the cylindrical cup slightly overflows. Then, without moving the tray, use a stainless steel ruler to scrape the surface of the sample once front and back to level it with the mouth of the cylindrical cup. Tap the cup to make the powder sink and ensure that no powder is lost or adhered to the outer wall. Finally, gently remove the round tray, take out the cylindrical cup, clean the outer wall with a brush, and place it on a balance to weigh it. After the data stabilizes, read the total mass of the cylindrical cup and the sample. The calculation formula is as follows: BD = (m 1- m0) / V;
[0128] BD——loose bulk density of the sample, g / cm 3 ;
[0129] m1——total weight of cylindrical cup and sample, g;
[0130] m0——mass of cylindrical cup, g;
[0131] V——internal volume of cylindrical cup, cm 3 .
[0132] 2. Tap density TD: Place a clean plastic funnel on the measuring cylinder, pour all the sample into the measuring cylinder through the funnel and ensure complete transfer, then immediately seal the measuring cylinder mouth with sealing film. Turn on the instrument, set the frequency to 200 times / minute, and tap 3000 times. After the tapping is completed, remove the measuring cylinder, read the scale volume of the three surfaces of the material and take the average value V. The calculation formula is as follows: Tap density calculation formula: TD=m / V;
[0133] TD——tapped density of the sample, g / cm 3 ;
[0134] m——mass of the sample, g;
[0135] V——Material volume, cm 3 .
[0136] 3. Compression degree S: Substitute the loose bulk density BD and tap density TD of the positive electrode active material into the formula S = (TD-BD) / TD to calculate the compression degree S of the positive electrode active material.
[0137] 4. Compacted density of positive electrode sheet: At 25°C and normal pressure (0.1MPa), the positive electrode active material, conductive carbon black, and binder polytetrafluoroethylene (PTFE) of each embodiment and comparative example were fully stirred and mixed at a mass percentage ratio of 95:2.5:2.5, and then put into a mixer for 1h to obtain a mixed product. The mixed product was then hot rolled four times to obtain a self-supporting film. Two self-supporting films were placed on the upper and lower surfaces of the carbon-coated aluminum foil, respectively, and heated and cured by a hot roller press to make the self-supporting film and the carbon-coated aluminum foil firmly adhered, that is, composited to obtain a positive electrode sheet. The positive electrode sheet was rolled to test its compacted density.
[0138] 5. Positive electrode matrix material D50: The particle size of the positive electrode matrix material was tested using a laser particle size analyzer (MasterSizer 3000).
[0139] 6. Determination of the chemical formula of the coating layer: First, the cleaned sample is subjected to a full spectrum scan in a high-resolution XPS instrument, followed by a high-resolution scan of the Li, M, P, and O elements. Through background subtraction and peak position fitting, the relative sensitivity factor (RSF) is used to convert the photoelectron intensity into atomic percentage, and the chemical formula of the coating layer is calculated.
[0140] 7. Coating thickness: A transmission electron microscope (TEM) is used to test the coating thickness of the positive electrode active material. The positive electrode active material is first dispersed in an anhydrous ethanol solution to obtain a dispersion. The dispersion is then dropped onto a copper mesh for drying and sampling. The electron beam generated by an electron gun in a high vacuum environment penetrates the sample and focuses on the image. The coating thickness is measured by observing the image on the display screen using the built-in calibration tool. The average value is calculated after measuring multiple areas to obtain the coating thickness.
[0141] 8. Test of the mass percentage of the positive electrode matrix material and the coating layer: The molar ratio of the M element can be obtained through ICP testing. The chemical formula of the coating layer and the matrix material is known and can be converted into the corresponding mass ratio.
[0142] 9. Discharge capacity and first coulombic efficiency: The positive electrode is punched into a small disc with a diameter of 12mm using a membrane tool. After drying and weighing, it is assembled into a button cell in a glove box under an Ar protective atmosphere using a 2025 button cell shell, a Li metal disc as the negative electrode, and a conventional high-voltage lithium cobalt oxide electrolyte. Charge to 4.3V at a constant current rate of 2C, then charge at a constant voltage at 4.3V to a current equal to 0.05C. The charging capacity at this time is recorded as the first cycle charging capacity. After standing for 5 minutes, discharge at a constant current rate of 2C to a voltage of 2.0V. The discharge capacity this time is recorded as the first cycle discharge capacity of the battery. The obtained discharge capacity / charge capacity is the first coulombic efficiency.
[0143] 10. Cycle performance: According to the method in the charge capacity test, the positive electrode active material is made into a positive electrode sheet, the negative electrode is made of graphite, and the separator polyethylene and the electrolyte (the electrolyte is LiPF6, the solvent is EC / DMC) form a full battery. At 25°C, it is charged to the upper limit voltage at a constant current of 1C, and then charged to the lower limit voltage at a constant voltage of 0.5C, and then discharged to the lower limit voltage at a discharge rate of 1C. Repeat this charge and discharge cycle 100 times, and measure the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 100th cycle. 100 The capacity retention rate after 100 cycles is Q=Q 100 / Q1*100%.
[0144] Figure 1 This is a scanning electron microscope image of the cross section of the positive electrode active material of Example 2 of the present invention.
[0145] from Figure 1 It can be seen that the positive electrode active material prepared in Example 2 of the present invention has good dispersibility.
[0146] Figure 2 This is a scanning electron microscope image of the cross section of the positive electrode active material of Comparative Example 1 of the present invention.
[0147] from Figure 2 It can be seen that the positive electrode active material prepared in Comparative Example 1 of the present invention has poor dispersibility.
[0148] Table 1
[0149]
[0150] It can be seen from Table 1 that, compared with the comparative example, the compression degree S of the positive electrode active material provided by the present invention satisfies 0.45≤S≤0.55, and has moderate compressibility during the compaction process, which can reduce the friction of the positive electrode active material, help reduce excessive contact and agglomeration between particles, make the particles more dispersed, and improve the fluidity of the positive electrode active material, so that the particles can be more evenly filled into the positive electrode sheet during the compaction process, which helps to increase the compaction density of the positive electrode sheet, thereby improving the energy density of the battery.
[0151] From the comparison between Examples 1-13 and Comparative Examples 1-3, it can be seen that the positive electrode active material provided by the present invention is applied to a battery to improve the discharge specific capacity, first coulombic efficiency and cycle performance of the battery.
[0152] Finally, it should be noted that those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses or adaptations of the present invention, which follow the general principles of the present invention and include common knowledge or customary technical means in the art not disclosed by the present invention, are not limited to the precise structure described above and shown in the drawings, and may be modified and changed in various ways without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A positive electrode active material, characterized in that: It includes a positive electrode base material and a coating layer existing on the surface of the positive electrode base material; The compression degree S of the positive electrode active material is 0.45≤S≤0.
55.
2. The positive electrode active material according to claim 1, characterized in that The chemical formula of the coating layer is Li x M y PO4, wherein M includes at least one of Ti, V, Co, and Zn, 0<x≤0.2, 0.5<y<1.
5.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The coating layer has a thickness of 1 nm to 5 nm.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The median particle size D50 of the positive electrode matrix material is 500nm-1500nm.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The positive electrode matrix material includes lithium-containing phosphate.
6. The positive electrode active material according to claim 5, characterized in that The lithium-containing phosphate includes at least one of lithium iron phosphate, lithium manganese phosphate, lithium vanadium phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, and lithium iron vanadium manganese phosphate.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that: The mass percentage of the positive electrode matrix material in the positive electrode active material is 99.4%-99.98%; And / or, the mass percentage of the coating layer in the positive electrode active material is 0.02%-0.6%.
8. The positive electrode active material according to any one of claims 1 to 7, characterized in that: The loose packing density of the positive electrode active material is 0.35 g / cm 3 -0.45g / cm 3 ; And / or, the tap density of the positive electrode active material is 0.75 g / cm 3 -0.85g / cm 3 .
9. A method for preparing a positive electrode active material according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Activating the positive electrode matrix material to obtain a first intermediate; 2) stirring the solution including the first intermediate, the M source and the P source uniformly, and filtering to obtain a second intermediate; wherein the M source is a metal organic compound including the M element; 3) Sintering the second intermediate to obtain the positive electrode active material; wherein the sintering temperature is 450° C.-650° C.
10. The method for preparing a positive electrode active material according to claim 9, characterized in that: The total molar ratio of the positive electrode matrix material to the M source and the P source is (200-3000):1; And / or, the sintering treatment time is greater than 6h-18h.
11. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 8 or the positive electrode active material prepared by the preparation method of the positive electrode active material according to claim 9 or 10.
12. The positive electrode sheet according to claim 11, characterized in that: The compaction density of the positive electrode sheet is greater than or equal to 2.3 g / m 3 .
13. A method for preparing a positive electrode sheet according to claim 11 or 12, characterized in that: The following steps are involved: 1) Forming a raw material containing a positive electrode active material into a self-supporting film; 2) Compounding the self-supporting film and the positive electrode current collector to obtain the positive electrode sheet.
14. A battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to claim 11 or 12 or a positive electrode sheet prepared by the method for preparing the positive electrode sheet according to claim 13.
Citation Information
Cited By
Method for mixing and coating electrolytic manganese dioxide, electrolytic manganese dioxide and application of electrolytic manganese dioxide
CN120565656A